2020
DOI: 10.1007/s13437-020-00206-y
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of low-level automation navigation functions upon vessel traffic services work practices

Abstract: The Sea Traffic Management (STM) Validation Project is a European-based initiative with ambitions to improve maritime safety and efficiency through information sharing in real time. The purpose of this paper is to evaluate the “STM services,” which can be categorized as low-level automated functions designed to improve information exchange between ship and shore. Full-scale simulated scenarios were developed and tested on 16 professional vessel traffic service (VTS) operators comparing VTS operations as they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…What impact on safety can applications, such as Icebreaker Assistance, have? The maritime industry is technology driven [42], and ensuring that new technology will support the operator rather than introduce unwanted risk is important. When asked about safety, the participants agreed that highlighting various types of critical operational information at the right time could improve safety.…”
Section: Discussionmentioning
confidence: 99%
“…What impact on safety can applications, such as Icebreaker Assistance, have? The maritime industry is technology driven [42], and ensuring that new technology will support the operator rather than introduce unwanted risk is important. When asked about safety, the participants agreed that highlighting various types of critical operational information at the right time could improve safety.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of three actual collisions on the high seas showed that situations of high complexity, which decrease human reliability, can be predicted well in advance, allowing for a safe resolution [ 20 ]. Based on the above-mentioned theories about VTS and shore-based services, there have been many studies that have discussed the future research directions of VTS [ 21 , 22 ]. The Sea Traffic Management (STM) Validation Project is a European-based initiative with ambitions to improve maritime safety and efficiency through information sharing in real time.…”
Section: Related Workmentioning
confidence: 99%
“…The Sea Traffic Management (STM) Validation Project is a European-based initiative with ambitions to improve maritime safety and efficiency through information sharing in real time. Katie Aylward et al discussed the role of STM service integration in changing the role of VTS operators in traffic conditions and the potential impact of STM service individuals on VTS operations from the perspective of social technology systems [ 22 ].…”
Section: Related Workmentioning
confidence: 99%
“…These functions provide additional information about surrounding traffic and allow information exchange between ships to enable operators to make more informed decisions based on real-time information. The results from the STM project indicate that, although several of the STM services were useful, they caused changes to existing work practices which could impact communication structures, workload, and situational awareness (Aylward et al, 2020a, 2020b). This work highlighted the need for an increased research focus on the potential impacts of low-level automation within the maritime socio-technical system.…”
Section: Introductionmentioning
confidence: 99%